An arms-race against resistance: leukemic stem cells and lineage plasticity - Waclawiczek, Alexander; Leppä, Aino-Maija; Renders, Simon; Trumpp, Andreas (Molecular oncology, 2024)
Acute myeloid leukemia (AML) therapy is undergoing rapid development, but primary and acquired resistance to therapy complicates the prospect of a durable cure. Recent functional and single-cell multi-omics approaches have greatly expanded our knowledge of the diversity of lineage trajectories in AML settings. AML cells range from undifferentiated stem-like cells to more differentiated myeloid or megakaryocyte/erythroid cells. Current clinically relevant drugs predominantly target the myeloid progenitor lineage, while monocyte- or stem cell-like states can evade current AML treatment and may be targeted in the future with lineage-specific inhibitors. The extent of aberrant lineage plasticity upon therapeutic pressure in AML cells in conjunction with hijacking of normal differentiation pathways is still a poorly understood topic. Insights into the mechanisms of lineage plasticity of AML stem cells could identify both therapy-specific and cross-drug resistance pathways and reveal novel strategies to overcome them.
Online veröffentlicht: 20. Februar 2024
Gesehen am 27.02.2025